Análisis de la estrategias en la gestión administrativa implementadas durante la crisis de la industria del petróleo en Colombia (2014-2017) por compañías operadoras del sector (2019)
The following document represents and compares the different strategies used by four companies dedicated to the oil market (Upstream, Midstream and Downstream) in Colombia with their net profit, in order to survive the oil prices drop in 2014-2017. Furthermore, it explains concepts about strategic management, global oil market, and why in the first place the prices dropped. Finally, it develops some conclusions about the strategies found.